Hemobilia pós-trauma - Serra,Márcio Canavarros (2002)
Our objective is to report a case of a patient, with a thoraco-abdominal gunshot wound with right hemothorax and liver lesion in the right lobe. The liver and the diafragm were sutured and the chest was drained. On the 9th post operative day the patient had hematemesis, jaundice and pain in the right upper quadrant of the abdomen. The abdominal ultrasound image with Doppler, revealed arteriobiliary fistulae. The diagnosis of hemobilia was made and the patient underwent embolization of the fistulae by liver arteriography.